Nove tehnologije v nevropsihološki diagnostiki in psihološki rehabilitaciji - Čižman Štaba, Urša (Rehabilitacija (Ljubljana), 2022)
In clinical psychology, technological innovations are increasingly being used in neuropsychological diagnostics, cognitive rehabilitation and psychotherapy. Most neuropsychological assessments involve at least one step of managing, assessing, or interpreting using computers or other technologies. The paper presents a set of technological interventions that are increasingly used both in Slovenia and around the world. Cognitive rehabilitation makes the most use of new technologies, such as computer software, virtual reality, computer-assisted neuropsychological diagnostics, smartphones and tablets. The most established technology in this field is computer-aided neuropsychological diagnostics, which enables better ecological validity and cost efficiency.
Keywords: cognitive rehabilitation; Computing Methodologies; kognitivna rehabilitacija; navidezna resničnost; neuropsychological diagnostics; Neuropsychology; nevropsihološka diagnostika; psihološka rehabilitacija; psychological rehabilitation; psychology; technology; tehnologija; virtual reality